A robust criterion for determining the number of static factors in approximate factor models - Lucia Alessi; Matteo Barigozzi; Marco Capasso (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2007)
We propose a refinement of the criterion by Bai and Ng [2002] for determining the number of static factors in factor models with large datasets. It consists in multiplying the penalty function times a constant which tunes the penalizing power of the function itself as in the Hallin and Lika [2007] criterion for the number of dynamic factors. By iteratively evaluating the criterion for different values of this constant, we achieve more robust results than in the case of fixed penalty function. This is shown by means of Monte Carlo simulations on seven data generating processes, including heteroskedastic processes, on samples of different size.
Keywords: C52; 330; Approximate factor models; Information criterion; Number of factors; Faktorenanalyse; Panelforschung; Modellierung; Dynamisches Modell; Theorie